2018
DOI: 10.1007/s00391-018-1432-6
|View full text |Cite
|
Sign up to set email alerts
|

Gewünschter Sterbeort, Patientenverfügungen und Versorgungswünsche am Lebensende: erste Ergebnisse einer Befragung von Pflegeheimbewohnern

Abstract: Residents view their nursing home as the place for dying in a much more positive light compared to frequent discussions contrasting population surveys and actual places of death. End of life prearrangements should be designed as a dynamic process that include persons of trust, nurses and general practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
2
0
7
Order By: Relevance
“…In a survey of German residents of nursing homes, 36.7% reported that they have written an advance healthcare directive, healthcare proxy, or advance care directive. 16 The representative population survey of the German Hospice and Palliative Care Association from 2017 showed also that 43% of the respondents had written an advance healthcare directive. 2 In the present survey, 55% of the respondents report that they have an advance healthcare directive, which is higher than the results of other surveys.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of German residents of nursing homes, 36.7% reported that they have written an advance healthcare directive, healthcare proxy, or advance care directive. 16 The representative population survey of the German Hospice and Palliative Care Association from 2017 showed also that 43% of the respondents had written an advance healthcare directive. 2 In the present survey, 55% of the respondents report that they have an advance healthcare directive, which is higher than the results of other surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Besonders relevant erscheint das bei Pflegeheimbewohner*innen mit einer Demenzprävalenz von über 50%, die mit steigendem Alter weiter zunimmt 1 2 3 4 . Bisher wird der Anteil der Pflegeheimbewohner*innen, die eine Vorausverfügung verfasst haben, in Deutschland mit 36,7–66,8% angegeben 5 6 .…”
Section: Hintergrundunclassified
“…Der Anteil der Patientenverfügungen/Vorsorgevollmachten wird in der neueren deutschen Literatur mit einer Spanne von 32,6% bis 69% angegeben 5 , 6, 96 7 8 9 10 14 18 . Eine Erklärung für die hohe Zahl an Vorausverfügungen (71%) in der vorliegenden Arbeit könnte in der zunehmenden Verbreitung des Wissens und der Akzeptanz von Vorausverfügungen in der Bevölkerung liegen sowie in dem Engagement der beteiligten Pflegefachkräfte und der jeweiligen HÄ begründet sein 19 .…”
Section: Diskussionunclassified
“…Im internationalen Vergleich variiert das Versterben von Heimbewohner*innen zwischen 6-77 % mit einem Median von 23 %, wobei Deutschland mit 29-30 % darüber liegt [22]. Heimbewohner*innen sehen Altenpflegeeinrichtung mehrheitlich als das Umfeld an, in dem sie auch versterben möchten [23], sodass die Ergebnisse zum Sterbeort der von uns Befragten positiv als Hinweis auf die Beachtung des Bewohnerwillens interpretiert werden können. So scheint in den beteiligten Einrichtungen ein zurückhaltender Umgang mit Krankenhauseinweisungen am Lebensende gepflegt zu werden, was auf eine an diesem Punkt gelebte Hospizkultur hindeuten könnte.…”
Section: Diskussionunclassified